Requirement of one functional RAS gene and inability of an oncogenic ras variant to mediate the glucose-induced cyclic AMP signal in the yeast Saccharomyces cerevisiae. - Mbonyi, K (1988)
Addition of glucose to Saccharomyces cerevisiae cells grown on a nonfermentable carbon source triggers a cyclic AMP (cAMP) signal, which induces a protein phosphorylation cascade. In a yeast strain lacking functional RAS1 and RAS2 genes and containing a bcy mutation to suppress the lethality of RAS deficiency, the cAMP signal was absent. Addition of dinitrophenol, which stimulates in vivo cAMP synthesis by lowering intracellular pH, also did not enhance the cAMP level. A bcy control strain, with functional RAS genes present, showed cAMP responses similar to those of a wild-type strain. In disruption mutants containing either a functional RAS1 gene or a functional RAS2 gene, the cAMP signal was not significantly different from the one in wild-type cells, indicating that RAS function cannot be a limiting factor for cAMP synthesis during induction of the signal. Compared with wild-type cells, the cAMP signal decreased in intensity with increasing temperature in a ras2 disruption mutant. When the mutant RAS2Val-19, which carries the equivalent of the human H-rasVal-12 oncogene, was grown under conditions in which RAS1 expression is repressed, the cAMP signal was absent. The oncogene product is known to be deficient in GTPase activity. However, the amino acid change at position 19 (or 12 in the corresponding human oncogene product) might also have other effects, such as abolishing receptor interaction. Such an additional effect probably provides a better explanation for the lack of signal transmission than the impaired GTPase activity. When the RAS2Val-19 mutant was grown under conditions in which RAS1 is expressed, the cAMP signal was present but significantly delayed compared with the signal in wild-type cells. This indicates that oncogenic RAS proteins inhibit normal functioning of wild-type RAS proteins in vivo and also that in spite of the presence of the RAS2(Val-19) oncogene, adenyl cyclase is not maximally stimulated in vivo. Expression of only the RAS(Val-19) gene product also prevented most of the stimulation of cAMP synthesis by dinitrophenol, indicating that lowered intracellular pH does not act directly on adenyl cyclase but on a step earlier in the activation pathway of the enzyme. The results obtained with the control bcy strain, the RAS2(Val-19) strain under conditions in which RAS1 is expressed, and with dinitrophenol show that the inability of the oncogene product to mediate the cAMP signal is not due to feedback inhibition by the high protein kinase activity in strains containing the RAS2(Val-19) oncogene. Hence, the present results show that the RAS protein in S. cerevisiae are involved in the transmission of the glucose-induced cAMP signal and that the oncogenic RAS protein is unable to act as a signal transducer. The RAS protein in S. cerevisiae apparently act similarly to the Gs proteins of mammalian adenyl cyclase, but instead of being involved in hormone signal transmission, they function in a nutrient-induced signal transmission pathway.